Fiscal decentralization and public sector efficiency: evidence from OECD countries - Antonis Adam; Manthos D. Delis; Pantelis Kammas (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper attempts to identify the effect of fiscal decentralization on public sector efficiency (PSE). We employ data envelopment analysis on a panel of 21 OECD countries over the period 1970-2000 to construct two alternative PSE indicators that reflect the governmental goals of economic performance and stability. In turn, using a novel technique that merges the methodologies of Simar and Wilson (2007) and Khan and Lewbel (2007), we regress the PSE scores obtained on an extensive set of alternative fiscal decentralization measures. Backed by strong empirical results, obtained from a number of different specifications, we contend that PSE is increasing with fiscal decentralization.
Keywords: C14; C24; H11; H50; 330; public sector efficiency; fiscal decentralization; semi-parametric models; Finanzföderalismus; Öffentlicher Sektor; Technische Effizienz; Wirtschaftspolitisches Ziel; Data-Envelopment-Analyse; OECD-Staaten